Marcas da enunciação e construção de sentidos em textos de divulgação científica: um estudo sobre a revista Ciência Hoje das Crianças - OLIVEIRA, Maria Elizete Melo de (2021)
In this research, we turn to the study of the enunciation marks used in the Scientific Dissemination Text for children. Therefore, we follow the theory of enunciation as a basis for understanding the enunciative choices used and projected in the construction of the enunciation, generating effects of orality senses. For this, we assume that the Scientific Dissemination Text emerged as a way to popularize science, taking scientific knowledge not only to the academic community, but also to other audiences, in this case, children, and therefore, the The text undergoes a reformulation, using enunciative strategies that make the language accessible to children so that they can understand the utterance. In order to carry out this work, we took as corpus the Scientific Dissemination Text taken from the Revista Ciência Hoje das Crianças, since enunciative marks are used in the constitution of the text and project effects of a sense of reality, of truth, of approximation between the interlocutors. In this context, the aim of this research is to analyze the enunciation marks present in Scientific Dissemination Texts as a mechanism that generates the effect of the sense of orality among the interlocutors. Therefore, we had as main theoretical basis authors such as Benveniste (1988; 1989; 1991), Greimas and Courtés (1979), Crestani (2010), Barros (2012), Fiorin (2016), and Flores (2020), Marcuschi (2008 ; 2010), Marcuschi and Dionísio (2007), Hilgert (2007; 2011; 2015), Bueno (1984), Leibruder (2002), Valério (2005), Mendes (2006), Giering (2009), Motta-Roth (2009 ), Sousa (2014) and Boff (2017). The methodological procedures for carrying out the analyzes are bibliographical in nature, in a qualitative approach and interpretive method, based on Prestes (2012) and Moita Lopes (1994). The results indicate that the enunciation marks are manifested in the written utterances through the enunciative choices made by the enunciator in the enunciative act. And, the enunciative choices used in the constitution of the written text, as well as the enunciation mechanisms projected in the utterance, evoke characteristics of spoken interactions, and generate a simulacrum of a face-to-face interaction, with an effect of orality, reality and truth. Furthermore, we found that orality and writing, even being of different linguistic nature, both complement each other and because they belong to the same linguistic system, we can find traces of each other.